Strategi Hukum Pengembangan Tambak Smart Silvofishery dalam Rehabilitasi Mangrove di Ibu Kota Nusantara - Hidayah, Rahmawati Al; Susmiyati, Haris Retno; Hardi, Esti Handayani; Diana, Rita; Palupi, Nurul Puspita (Seminar Nasional Lahan Suboptimal, 2023)
Al-Hidayah, R., Susmiyati, H. R., Hardi, E. H., Diana, R., Palupi, N. P. (2023). Legal strategy for smart silvofishery pond development in mangrove rehabilitation in the capital city of nusantara. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang  21 Oktober 2023. (pp. 616-625).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Mangrove ecosystem areas in The Nusantara Capital area have not been protected, especially those located in traditional fish pond cultivation development areas. The aimed of this research is to analyse the legal problems of developing smart silvofishery ponds in mangrove rehabilitation and formulate legal strategies to overcome them. The method is a socio-legal research method with a qualitative approach used. The research results show that legal problems in the development of smart silvofishery ponds occur as a result of the absence of specific regulations governing this matter. Government and the community feel that they have no obligation to develop smart silvofishery ponds which will affect mangrove rehabilitation efforts. Besides that, fish farming operators do not understand the concept and urgency of smart silvofishery. Facing these problems, legal strategies are important to implement. Referring to the theory of legal formation, the law aims to integrate and coordinate various interests in society because in a traffic of interests, protection of certain interests can only be done by limiting various interests on the other side. The legal strategy is developed by establishing regulations at the central, regional and local levels regarding legal protection, both preventive and repressive. Preventive legal protection includes provisions that are preventative (prohabited) and repressive legal protection that is punitive (sanction). Multi-stakeholder roles and meaningful community participation are also needed.